Interplay of Trans- and Cis-Interactions of Glycolipids in Membrane Adhesion - Kav, Batuhan; Demé, Bruno; Gege, Christian; Tanaka, Motomu; Schneck, Emanuel; Weikl, Thomas R. (Frontiers in Molecular Biosciences, 2021)
Glycolipids mediate stable membrane adhesion of potential biological relevance. In this article, we investigate the trans- and cis-interactions of glycolipids in molecular dynamics simulations and relate these interactions to the glycolipid-induced average separations of membranes obtained from neutron scattering experiments. We find that the cis-interactions between glycolipids in the same membrane leaflet tend to strengthen the trans-interactions between glycolipids in apposing leaflets. The trans-interactions of the glycolipids in our simulations require local membrane separations that are significantly smaller than the average membrane separations in the neutron scattering experiments, which indicates an important role of membrane shape fluctuations for glycolipid trans-binding. Simulations at the experimentally measured average membrane separations provide a molecular picture of the interplay between glycolipid attraction and steric repulsion of the fluctuating membranes probed in the experiments.